1999
DOI: 10.1002/(sici)1521-3889(199911)8:7/9<707::aid-andp707>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Disorder induced ferromagnetism

Abstract: We study the influence of on-site disorder on the magnetic properties of the ground state for restricted geometries. We find that for two dimensional systems disorder enhances the spin polarization of the system . The tendency of disorder to enhance magnetism in the ground state may be relevant to recent experimental observations of spin polarized ground states in quantum dots.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In 2D the influence of the spin background is non-commutative and therefore much more complex. This leads to ferromagnetic GS for one hole [1] and to disorder induced ferromagnetism for higher hole concentration [6]. It was also shown that the energy of spinless fermions is minimized when the applied magnetic flux is half the flux period, again, for any realization of disorder.…”
Section: Lieb and Mattismentioning
confidence: 98%
“…In 2D the influence of the spin background is non-commutative and therefore much more complex. This leads to ferromagnetic GS for one hole [1] and to disorder induced ferromagnetism for higher hole concentration [6]. It was also shown that the energy of spinless fermions is minimized when the applied magnetic flux is half the flux period, again, for any realization of disorder.…”
Section: Lieb and Mattismentioning
confidence: 98%
“…In this paper we study the effect of disorder on the enhancement of the spin polarizability of small interacting systems. For one dimensional infinite U Hubbard mod-els, disorder does not essentially change the magnetization behavior [9]. On the other hand, for two dimensional systems, it is found that sufficiently strong disorder suppresses the singlet-favoring effects and the spin polarization of the system increases.…”
mentioning
confidence: 89%
“…Let us first sketch the situation in 1D. If periodic BC are imposed in 1D, the problem of m interacting electrons (at U = ∞) can be mapped onto a system of m non-interacting spinless fermions on 1D ring with fluxes Φ/Φ 0 = 2πj/m (j = 0, , m − 1), where the GS energy corresponds to the flux j with the lowest energy [9]. This mapping shows that the effect of the spin background in 1D is trivial, and does not depend of the strength of disorder.…”
mentioning
confidence: 99%
See 1 more Smart Citation